The Effect of the Traditional Sack Race Game on the Lower Limb Muscle Strength of Fifth-Grade Elementary School Students - Acep Abdul Aziz; Yopa Taufik Saleh; Rahmat Permana (BASICA, 2026)
This study aims to examine the impact of physical activity based on local wisdom, specifically through the traditional sack race, on lower-limb muscle strength in Physical Education, Sports, and Health (PJOK) classes for fifth-grade elementary school students. The intervention was designed in a structured manner, following the principle of progressive overload, and implemented over six sessions. A quantitative approach using a True Experimental Design via a Pretest-Posttest Control Group Design was applied in this study. The entire population of 28 fifth-grade students at SDN Cicariu was included as participants using total sampling, who were then randomly assigned to an experimental group (n = 14) and a control group (n = 14). The experimental group received a learning program based on the traditional sack race game, while the control group followed conventional Physical Education (PJOK) instruction. Data on lower-body muscle strength were collected via the vertical jump test, which was subsequently analyzed using descriptive statistics and the non-parametric Mann–Whitney U test at a significance level of 0.05. The research results showed an upward trend in the average scores for both groups; however, the experimental group recorded a significantly higher percentage increase of 16.66% compared to the control group, which increased by only 5.36%. Through the Mann–Whitney U test, an Asymp. Sig. A value of 0.089 (p > 0.05) was obtained. This study concludes that physical activity through sack races is descriptively effective in stimulating lower limb muscle strength in elementary school-aged children. Implicitly, traditional games packaged systematically can be adopted by physical education teachers as a recreational yet educational alternative for physical activity to optimize students’ physical capacity without relying on expensive facilities.